Quand une profession taiseuse se dévoile sur le Web : les ethè discursifs élaborés dans les blogs de policiers - Pierre-Yves Connan; Guillaume Le Saulnier; Benoît Verdier (Itinéraires)
The paper deals with the reconfiguration of professional discourses, as a result of the use of blogs and social media by professional groups. Using both discourse analysis and research interviews, it studies a corpus of five blogs written by French policemen. Hidden behind pseudonyms, the authors tell their occupation and themselves candidly. They produce a first-person account of the condition of “street cops.” For that purpose, they use discursive self-presentation strategies, building different images of themselves. These enunciation strategies aim to create a link with the readers, but also to appear as legitimate enunciators able to speak on behalf of the profession.